2020
DOI: 10.1080/1343943x.2020.1740601
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced effect of farmyard manure application on P availability to rice for paddy soils with low total C and low pH in the central highlands of Madagascar

Abstract: Farmyard manure (FYM)mixtures of animal droppings, crop residues, and fodder that are piled nearby homesteadsis a major nutrient source for smallholder farmers in Sub-Saharan Africa. However, its application effect has not been fully understood on typical P-deficient soils in tropics and in particular under anaerobic conditions. This study assessed the effect of FYM on irrigated rice in relation to soil propertiesoxalate-extractable P (P Ox), pH, and total C (TotC)that are important indicators of soil P defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Sorghum biomass and grain yields in the NK were 34 and 27% lower, respectively, than those in the NPK treatment, highlighting the importance of P nutrition in the studied environment, further confirming that P is a limiting nutrient in the soil. Many studies have highlighted the significant contribution of improved P uptake to crop grain yields in Africa 45 , 46 . In addition, we observed 25 and 23% decreases in biomass and grain yield, respectively, in the NK compared to in the P-COMP-SOIL.…”
Section: Discussionmentioning
confidence: 99%
“…Sorghum biomass and grain yields in the NK were 34 and 27% lower, respectively, than those in the NPK treatment, highlighting the importance of P nutrition in the studied environment, further confirming that P is a limiting nutrient in the soil. Many studies have highlighted the significant contribution of improved P uptake to crop grain yields in Africa 45 , 46 . In addition, we observed 25 and 23% decreases in biomass and grain yield, respectively, in the NK compared to in the P-COMP-SOIL.…”
Section: Discussionmentioning
confidence: 99%
“…However, the strategy of adding extra C to the waterlogged soils was effective at some points during the incubation time and for the four soils in which the cellulose treatment surpassed the other treatments in solubilizing P. Similarly, the observation with the values in the control treatment were equal to or below those of the cellulose treatment in all soils, illustrating P solubilization due to amplified Fe reduction (Figure 2). This was most pronounced in S4, which could be attributed to its low C content (Mohammadi et al., 2009; Rakotoson and Tsujimoto, 2020; Vanden Nest et al., 2014). The rate of P solubilization due to OM2 addition was similar to that of cellulose addition, suggesting possible P immobilization due to a high C:P ratio, of around 386.5, and it is a low P content (1.84 g kg –1 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, a few of studies have focused on strategies to overcome the problem of P deficiency for lowland rice production, in particular by exploring the potential benefits of locally available organic resources. Although FYM application reportedly increases P availability in irrigated rice (Andriamananjara et al., 2016), Rakotoson and Tsujimoto (2020) found that the extent to which an increase in P availability led to an increase in biomass and yield was highly dependent on the soil characteristics. Farmers in SSA, including Madagascar, utilize extensive organic resources for fertilization, which affect crop production differently depending on various soil factors.…”
Section: Introductionmentioning
confidence: 99%
“…This is certainly the case in Madagascar where P deficiency is widespread, possibly due to high levels of P-fixing element such as iron (Fe), aluminum (Al) and/or oxyhydroxides [ 6 ]. This problem is exacerbated by the continual removal of organic residues and limited application of organic matter and/or fertilizer inputs [ 7 9 ]. The nutritional deficiency in soil could be alleviated through fertilizer application; however, the cost of fertilizers is often higher in SSA compared to other regions and therefore access to fertilizers is limited for resource-poor farmers in small scale farming systems.…”
Section: Introductionmentioning
confidence: 99%